Pangkalan Data Pustakawan Berbasis Ms-Access 2007 - Ferina, Deby; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper aims to improve the effectiveness of the librarians data searching in a certain database, to make IPI easier the supervise its members. Microsoft Access was used to build such database. Considering that Microsoft Access is available in windows operating system. The design of the database is created with attention to typography and coloring rules. The data was gathered by using observation and librarians interviewing. The data analyzed descriptively. It is concluded that (1) IPI cannot supervise its members maindly, (2) the data is suitable to IPI in supervising its members easily. Besides, the members can also access database as well. Â Keywords: database; searchin; librarians; IPI Â